2017
DOI: 10.4314/ijbcs.v11i1.36
|View full text |Cite
|
Sign up to set email alerts
|

Ecological effects of oil spill on water and sediment from two riverine communities in Warri, Nigeria

Abstract: The ecological effects of oil spill in the environment were studied in Warri riverine areas of Ubeji and Jeddo, Delta State, where an oil spill occurred and cleanup or remediation was not carried out for over a year prior to this evaluation. The American Public Health Association (APHA) and the American Society for Testing and Materials (ASTM) methods were employed for the laboratory test for organics [polyaromatic hydrocarbon; total petroleum hydrocarbon (TPH)] and heavy metals in the water and sediment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…This portrayed that the petroleum had negative consequences on the simulated aquatic ecosystem. A similar trend was reported by Ogeleka et al (2017), as a result of oil spills in Niger Delta waters. The TPH concentration of the contaminated water was higher than the maximum approved limit (10 mg/L) by the Nigeria Department of Petroleum Resources (DPR) for water bodies.…”
Section: Resultssupporting
confidence: 87%
“…This portrayed that the petroleum had negative consequences on the simulated aquatic ecosystem. A similar trend was reported by Ogeleka et al (2017), as a result of oil spills in Niger Delta waters. The TPH concentration of the contaminated water was higher than the maximum approved limit (10 mg/L) by the Nigeria Department of Petroleum Resources (DPR) for water bodies.…”
Section: Resultssupporting
confidence: 87%
“…For example, Ogeleka et al. (2017) studied the present situation in Warri riverine areas of Ubeji and Jeddo, where an oil spill occurred and remediation was not carried out for over a year. The authors reported that the total petroleum hydrocarbons (TPH) in the sediment was >1000 ppm in Jeddo and > 48 ppm in Ubeji which exceeds the 10 ppm allowable limits set by the DPR, while the total PAHs was 0.012 ppm in Ubeji and 0.026 ppm in Jeddo.…”
Section: Technologies For the Remediation Of Crude Oil Spillsmentioning
confidence: 99%
“…The vast area of mangrove swamps and arable land in Nigeria has been devastated due to soil spillage, causing serious environ-mental insecurity (Aniefiok et al, 2018). The environmental hazards associated with oil pollution are dependent on the concentration and volume of oil spilled, the biochemical and physical properties of the soil/water, the presence of natural remediating agent(s), and the prevailing environmental conditions (Ogeleka et al, 2017;Akpomrere and Uguru, 2020a;Akpoghelie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%